A.A.B. Sutedja File: Gubernur Bali Pertama dalam Lipatan Sejarah - Slamat Trisila, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This paper reveals a portion of political chapter AA BagusSutedja of Puri Negara, a royal household in Jembrana, WestBali. Sutedja was the first governor of Bali, the provincialisland officiated in 1959, which previously had been partof the Lesser Sunda Island Province. In this article we learnSutedja’s short, yet skyrocketing political career from a lowlevelgovernmental official and then built his own way to bethe island first governor. His appointment as the governor wasthe result of then President Soekarno’s political scenario inimplementing the policy of the central government in Jakarta.When the 1965’s political tragedy struck in Jakarta that topplethe president, Sutedja suffered similar fate. The governor notonly lost his position, but was tragically kidnapped and wasbelieved to have been killed. Till these days his where-aboutremains a mystery in Bali’s dark history.
Keywords: A.A.B. Sutedja; Bali governor; political map; power; violence